The illustrious academic Dr. Clemente Inclán and Costa. The Magnificent Rector - Miguel Angel Velis Diaz (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: During the period 1944 -1962, the Rector of the University of Havana was a doctor/pediatrician: Dr. Clemente Inclán and Costa.  He was considered one of the most important figures in the Cuban medicine, a solid pillar of the Cuban School of Pediatrics, an internationally prestigious doctor, and pride of the National Medicine. Objective:  A retrospective, historical study was carried out with the aim of describing the life and academic work of the illustrious figure of Dr. Inclán.   Material and Method:  Documental and historical-logical analyses were used.   Conclusions:  It is concluded that this doctor is one of the most important personalities in the history of teaching in the Cuban medicine of the 20th century and also, in the history of the current University of Medical Sciences of Havana.  Dr. Inclán is, undoubtedly, a theoretical and practical referent, an example and a behavior model to follow for the new generations of physicians, dentists, male nurses, technicians and the national and international graduates of the Cuban Universities of the Medical Sciences at present.  Keywords: academic, scientific, magnificent rector, pediatrics, solid pillars.